A self-determination theoretical approach into survival strategies of on-campus and off-campus students from low-income families - Ravhuhali, F.; Nendauni, L.; Sikhwari, T. D.; Lavhelani, N. P.; Dama, N. G.; Matodzi, T.; Manyage, T. (South African Journal of Higher Education, 2021)
An enormous number of students from rural-based universities are drawn from provinces which are primarily regarded as rural provinces in South Africa, due to underdevelopment which is rhetorically blamed on the legacy of apartheid. Moreover, a vast number of these students are enrolled at universities as first generation and largely come from low-income families, characterised by elements of poverty. These students often experience literacy problems, mostly because of the type of high school they attended. Be that as it may, these students need to survive, hence, the need for this type of exploration, which sought to understand survival strategies of students from low -income families in a South African rural-based university. This study or article is solely rooted on Self-determination theory as the theoretical point of departure. Nevertheless, it also incorporates elements of Bandura’s Social cognitive theory as a supplementary theory. Following a qualitative research design, the population of the study comprised students from low-income families. Purposive and snowball sampling procedures were used to select students’ questionnaires with open-ended questions, whilst content analysis was used as a data analysis tool. The findings of the article exhibit several complexities and difficulties that students from low-income families endure such as lack of funds, materials and being exposed to crime. Students make use of financial aid schemes, peer support groups and university’s financial aid to survive. The article has implications for higher education institutions on how they can adopt a variety financial aid practices that could be tailored towards assisting on-campus and off-campus students from low-income families.